Explorations in Post-Secular Metaphysics - Bengtson, Josef. author. aut Link
IX, 211 p.
Keywords: This book explores the metaphysical assumptions that underlie different interpretations of the relationship between religion and the secular, faith and reason, and transcendence and immanence. It explores different answers to the question of how people of diverse religious and cultural identities can live together peacefully.